2016
DOI: 10.3390/ijms17121974
|View full text |Cite
|
Sign up to set email alerts
|

Future Prospects for Scaffolding Methods and Biomaterials in Skin Tissue Engineering: A Review

Abstract: Over centuries, the field of regenerative skin tissue engineering has had several advancements to facilitate faster wound healing and thereby restoration of skin. Skin tissue regeneration is mainly based on the use of suitable scaffold matrices. There are several scaffold types, such as porous, fibrous, microsphere, hydrogel, composite and acellular, etc., with discrete advantages and disadvantages. These scaffolds are either made up of highly biocompatible natural biomaterials, such as collagen, chitosan, etc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
327
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 466 publications
(333 citation statements)
references
References 285 publications
(390 reference statements)
0
327
0
6
Order By: Relevance
“…Elasticity is one of the most important parameters for bandage like scaffolds for their practical applicability. Therefore, since direct application on the skin is aimed, bandage like scaffolds should have similar mechanical features in order to be compatible with its surroundings . Thus, this synergy can also support the compatibility in the cellular manner due to ensuring similar environmental factors since the skin is constantly in motion caused by the movements of the bearer and therefore, scaffolds designed to host cell adhesion needs to be enduring and corresponding to the motion.…”
Section: Resultsmentioning
confidence: 99%
“…Elasticity is one of the most important parameters for bandage like scaffolds for their practical applicability. Therefore, since direct application on the skin is aimed, bandage like scaffolds should have similar mechanical features in order to be compatible with its surroundings . Thus, this synergy can also support the compatibility in the cellular manner due to ensuring similar environmental factors since the skin is constantly in motion caused by the movements of the bearer and therefore, scaffolds designed to host cell adhesion needs to be enduring and corresponding to the motion.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that carbon-based nanomaterials are prominent due to their ease of functionalization, and a comparative study suggested that ND has better biocompatibility than any other carbon nanoparticles (Ho, Wang, & Chow, 2015;. Therefore, excellent biocompatibility, superior physicochemical property, ease of availability, bactericidal activity, and nanoscale particle size (diamond nucleus size 4-6 nm) have made ND an ideal candidate for biomedical applications (Chaudhari et al, 2016;Liu et al, 2014). One of the key properties of ND is photoluminescence originating from structural defects, atomic vacancies (NV) and surface chemistry.…”
Section: Applications In Biomedical Areasmentioning
confidence: 99%
“…Anti‐inflammatory and antifibrotic factors and stem cells can be applied in a scaffold. Scaffolds are used as an artificial ECM, which supports cell attachment, proliferation, and differentiation of cells . The scaffold guides the newly formed tissue and allows ingrowth of blood vessels and nerves crucial for cell survival.…”
Section: Clinical Challenges For Scaffold‐based Cord Blood Stem Cellsmentioning
confidence: 99%